Pocket book of integrals and mathematical formulas - Tallarida, Ronald J. (Advances in applied mathematics, 2015)
Pocket Book of Integrals and Mathematical Formulas, 5th Edition covers topics ranging from precalculus to vector analysis and from Fourier series to statistics, presenting numerous worked examples to demonstrate the application of the formulas and methods. This popular pocket book is an essential source for students of calculus and higher mathematics courses. It also provides an easy-to-use, accessible reference for mathematicians, engineers, scientists, and others seeking vital mathematical formulas, concepts, and definitions.